King Henry V - Shakespeare, William, 1564-1616 (Salt Lake City, UT : Project Gutenberg, 1998)
"King Henry V" by William Shakespeare is a history play written circa 1599. It follows the young King Henry V of England as he claims the French throne and leads his outnumbered army to face the French at the Battle of Agincourt during the Hundred Years' War. The final play in a tetralogy, it shows Henry's transformation from the wild prince of earlier plays into a determined warrior-king who must inspire his troops and bear the moral weight of leadership. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Henry_V_(play)
Release date is 1998-11-01
the PG Shakespeare Team, a team of about twenty Project Gutenberg volunteers.
Keywords: Henry V, King of England, 1387-1422 -- Drama; Great Britain -- Kings and rulers -- Drama; Great Britain -- History -- Henry V, 1413-1422 -- Drama; Historical drama